A STUDY ON THE EFFECT OF MOTIVATIONAL STRATEGIES ON ORGANIZATION PERFOMANCE: A CASE STUDY OF PUBLIC UNIVERSITIES IN NAKURU COUNTY, KENYA - CHERAISI, LINET; Simon, Kipchumba; Ayuo, Amos (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Motivated employees can help make an organization competitively more value added and profitable. The aim of the study was to determine the effect of motivational strategies on organizational performance in public universities in Nakuru County. The target population consisted of managers, academic staff and non-academic staff in public universities in Nakuru County. Purposive sampling was used to choose the universities. Stratified random sampling and simple random sampling techniques was used to determine the sample of each stratum of various sub population of total sample unit size of 435. A questionnaire was used to collect data, the instrument was pilot tested to ascertain the content, construct and face validity. Reliability coefficient 0.7 and above was accepted. Descriptive statistics which includes percentages, frequencies, means, standard deviation and inferential statistics namely; t-test, Pearson product moment correlation and multiple regressions were used to analyze the data. The results showed that public universities in Nakuru County motivational strategies showed Weak positive relationship against performance.